Exploration of the Topical Nanoemulgel Bearing with Ferulic Acid and Essential Oil for Diabetic Wound Healing - Urati Anuradha; Valamla Bhavana; Padakanti Sandeep Chary; Nitin Pal Kalia; Neelesh Kumar Mehra (Pathophysiology)
Aim: To investigate the anti-inflammatory, antioxidant, and diabetic wound healing properties of the novel topical formulation [Ferulic acid-loaded nanoemulgel (DLMGO-G)]. Methods: Ferulic acid nanoemulsion developed with lemongrass oil is investigated in diabetic wound healing. Further nanoemulsion is incorporated into 1% carbopol® 934 to obtain the DLMGO-G. Nanoemulsion was characterized for particle size, and polydispersity index (PDI) was obtained by Malvern Zetasizer (Zetasizer Nano ZS, Malvern, AL, USA), and morphology by TEM (JEM 1400, JOEL, Akishima, Japan). Furthermore, in vitro cell line and in vivo studies were carried out. Results: The developed nanoemulsion showed a globule size of 28.04 ± 0.23 nm and PDI of 0.07 ± 0.01. The morphology of nanoformulations by TEM confirmed the spherical and uniform nature. Further, the nanoformulation in in vitro cell line experiments revealed that the IC50 value was increased by 1.52 times compared to the drug solution. The treatment groups have shown that fibroblast morphologies were spindle-shaped, suggesting that nanoformulation was compatible with the cells and developed normally on nanoformulation. It also reduced ROS with improved internalization more than the control group. The in vitro wound healing model also revealed that nanoformulation had better wound healing activity. In the in vivo diabetic wound studies on male SD rats, the levels of inflammatory markers such as TNF-α, IL-6, IL-22, and IL-1β declined significantly when treated with DLMGO-G. IL-10 levels significantly increased compared to the diseased group, and MMP-9 levels were remarkably decreased compared to the diseased group. Furthermore, histopathological studies showed the regeneration and granulation of tissues. Conclusions: Thus, these findings indicate that FA-loaded nanoemulgel greatly accelerates the healing of wounds in diabetic rats.